AMAP Litter and Microplastics Monitoring Guidelines. Version 1.0. - Unkn Unknown (Arctic Monitoring and Assessment Programme, 2021)
Purpose of the guidelines The purpose of the guidelines is to review existing knowledge and provide guidance for designing an Arctic monitoring program that will track litter and MP. The topics of litter, plastic pollution, and MP are addressed in many fora, including several of the Arctic Council working groups: Arctic Monitoring and Assessment Programme (AMAP; https://www.amap.no/documents/doc/amap-assessment-2016-chemicals-of-emerging-arctic-concern/1624), Protection of the Marine Environment (PAME, 2019), and Conservation of the Arctic Flora and Fauna (CAFF). The development of an Arctic monitoring program and its technical approaches will be based on the work that already exists in other programs such as those of OSPAR, the Helsinki Commission (HELCOM), the International Council for the Exploration of the Sea (ICES), the Organisation for Economic Co-operation and Development (OECD), and the United Nations Environment Programme (UNEP). Plastic pollution is typically categorized into items and particles of macro-, micro-, and nano-sizes. These guidelines address macrosized litter as well as MP (< 5 mm), essentially including smaller size ranges (> 1 μm). However, determination of nanoplastic (< 1 μm) particles is still hampered by technical challenges, as addressed in Section 4.3 Analytical methods, and thus not currently considered in the current recommendations. Although most studies have addressed marine litter and MP, these guidelines also comprise the Arctic’s terrestrial and freshwater environments.